2018
DOI: 10.1038/s41598-018-20155-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of low energy radiation response of AlAs, GaAs and GaAs/AlAs superlattice and the damage effects on their electronic structures

Abstract: In this study, the low energy radiation responses of AlAs, GaAs and GaAs/AlAs superlattice are simulated and the radiation damage effects on their electronic structures are investigated. It is found that the threshold displacement energies for AlAs are generally larger than those for GaAs, i.e., the atoms in AlAs are more difficult to be displaced than those in GaAs under radiation environment. As for GaAs/AlAs superlattice, the Ga and Al atoms are more susceptible to the radiation than those in the bulk AlAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Gallium Arsenium (GaAs), as a direct band gap semiconductor material, shows high application value in optoelectronic devices and nuclear microwave devices due to its suitable band gap, high electron/hole mobility, and photoelectric conversion efficiency [1][2][3][4][5]. The solar cells, photodetectors, light-emitting diodes and field-effect transistors based on GaAs have been widely applied in aerospace industry.…”
Section: Introductionmentioning
confidence: 99%
“…Gallium Arsenium (GaAs), as a direct band gap semiconductor material, shows high application value in optoelectronic devices and nuclear microwave devices due to its suitable band gap, high electron/hole mobility, and photoelectric conversion efficiency [1][2][3][4][5]. The solar cells, photodetectors, light-emitting diodes and field-effect transistors based on GaAs have been widely applied in aerospace industry.…”
Section: Introductionmentioning
confidence: 99%
“…Mitra and Stark found that the presence of vacancies enhanced the Ga/Al intermixing in GaAs/AlAs SL, resulting from the proposed two-atom ring mechanism of diffusion [ 16 ]. Recently, an AIMD simulation of radiation response of GaAs/AlAs SL has been carried out [ 17 ], in which the minimum energies for each atom to be permanently displaced from its lattice site have been determined, the pathways for defect generation have been provided, and the types of created defects have been identified. It revealed that the created Ga (or Al or As) Frenkel pair and As Ga -Ga As antisite pair have profound effects on the density of state distribution and band structure of GaAs/AlAs SL [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, as shown in Figure 2b, except of forming the MnAs NCs in the former (Ga,Mn)As shell and the outermost GaAs shell, an excess of Mn accumulates also at the NW surface. There is no direct comparison of the diffusion coefficients of Mn in GaAs and in AlAs available in the literature, but a compilation of theoretical and experimental values of the cohesive energy given in ref 32 , clearly indicates that AlAs has a higher cohesion energy than GaAs, which may result in the lower diffusion coefficient of Mn in (Ga,Al)As in comparison to that in GaAs. 22,33 Since TEM/STEM images are the planar projections of 3D structures, it is very challenging to prepare an ultra-thin specimen cut precisely through a small NC of interest without the surrounding WZ-GaAs matrix.…”
Section: Resultsmentioning
confidence: 99%